Gerações militantes : bases partidárias Petistas e Tucanas em São Paulo. - Locatelli, Luís Gustavo Bruno (Universidade Federal de São Carlos, 2017)
This research investigates the current militant frame of the PT and PSDB in Sao Paulo state, comparing them at different moments of their party path: youth and adult militancy – emphasizing the dimension "party on the ground face”. The research aims to fill two gaps of the current literature: first, contribute to the understanding of the profile and to the content of the performance of affiliated people in political parties; second, determine what are the impacts of generational changes in the Brazilian democracy, particularly in relations between young people and democratic institutions, specifically the man effects on internal life of the Sao Paulo's political parties. For this objective, we compared two surveys: one with young militants (respondents with a means age of 24 years) and another with adults (mean age 44 years) and the data obtained at Electoral Court (TSE) regarding the age groups of the members (2008 to 2016) and the age of entry of active members in 2014. The main findings are: aging tendency of both party memberships; disparity of civic resources of members and young members’ vis-à-vis the electorate; predominance of the mobilization by the collective incentives in both surveys. In addition, the relevant impacts of belief systems and internal rules at different levels of mobilization.
Militants generations: partisan bases PT and Tucanas in Sao Paulo
Keywords: Partidos políticos; Participação política; Organização partidária; Juventude; Militância partidária; Political parties; Political participation; Party organization; Party membership; Youth political participation; CIENCIAS HUMANAS::CIENCIA POLITICA